Biomimetic layered, ecological, advanced, multi-functional film for sustainable packaging - Puneet S. Dhatt; Acadia Hu; Cheng Hu; Vincent Huynh; Susie Y. Dai; Joshua S. Yuan (Nature Communications)
Abstract Plastic pollution is one of most daunting sustainability challenges. Multi-functional and biodegradable plastics are critical for both desirable end-of-life outcomes and petrochemical plastics replacement. Current bioplastics are either: short of mechanical properties, like polyhydroxybutyrate (PHB); lack room temperature biodegradability, like polylactic acid (PLA); or lack the functionality to create additional values. Here, we present the bioinspired Layered, Ecological, Advanced, and multi-Functional Film (LEAFF), for sustainable plastic packaging. This biomimetic composite, based on the structure of the natural plant leaf, synergistically improves mechanical strength while empowering PLA for rapid ambient soil biodegradability, achieving complete degradation in 5 weeks. The film is also highly transparent and water stable, and achieves high gas barrier properties to improve food shelf life and reduce waste. The biomimetic design showcases the synergistic advantage leveraged by the LEAFF’s multilayer structure to enhance mechanical performance while simultaneously retaining biodegradability and achieving multifunctionality for broad applications.